FINANCING RISK MANAGEMENT ANALYSIS ON BMT LA TANSA GONTOR PONOROGO - Ahmad Wafi Ahdalloh; Rahma Yudi Astuti (Islamic Business and Management Journal, 2019)
The current development of financial institutions, especially the Baitul Maal Wa Tamwil (BMT) despite the encouraging developments of a BMT is often hampered by most classic problems such as weak member participation, weak supervision and poor risk management. These problems are identified potential risks. So that departing from these problems, BMTs should be able to mitigate risk. Furthermore, for a BMT that is engaged in a savings and loan business is a risky financial service’s industry, therefore BMT should properly implement risk management.The formulation of the problem in this research is how the application of risk management at BMT La Tansa Gontor and how the application of risk management in overcoming the problematic financing at BMT La Tansa Gontor. The purpose of this study is to analyze how the application of risk management at BMT La Tansa Gontor, and to analyze how the application of risk management in overcoming problematic financing at BMT La Tansa. This type of research is field research, carried out with the conditions. Data were obtained from interviews with the Financing and Accounting Manager at BMT La Tansa. This research is also supported by library research that aims to collect data or information with the help of material, for example notes, documents, and other references related to risk management data for financing at the BMT La Tansa.The results of this study, BMT La Tansa has implemented risk management by conducting risk identification, risk measurements, risk monitoring, risk management information systems and risk control. This event is proven to minimize the occurrence of financing risk or problem financing, although the risk management of the financing has not been implemented properly, because in its implementation there are still ways to overcome problems with the family system. This event is actually lacking and slightly violates the rules in the application of financing risk management, but even though it feels more focused on the Islamic shariah(Fedro,2019), it would be better to be given extra strict and strict provisions in conditions, guarantees, and policies so that the sustainability of BMTs runs more effectively, so the congestion rate every year decreases, because with the existence of good risk management it will be able to minimize the occurrence of financing risks.